Helbredelsen - Finsten Jensen, Marie (K&K - Kultur og Klasse, 2023)
On November 29, 2020, 500 inhabitants gathered in a parade around the public housing neighborhood AKB Lundtoftegade in Copenhagen. Uniting spiritual, aesthetic, and political forms and under the name The Healing, the inhabitants fought against the Danish government’s so-called ”Ghetto Law” – a set of comprehensive laws and policies targeting low-income, largely minority public housing neighborhoods. The present paper examines The Healing using Judith Butler’s elucidation of transient, public assembly and precarity – in this case, the ”Ghetto Law’s” destruction of the conditions of livability – in Notes Toward a Performative Theory of Assembly (2015). While The Healing as a public assembly exemplifies the critical potential of a transient, unexpected political and aesthetic assembly, the paper emphasizes how the aesthetic and spiritual elements help to ensure that The Healing can be repeated – that the fight against the ”Ghetto Law” can be recurring, caring, and healing. The Healing, I argue, is thus both a transient prefiguration, and a proof of AKB Lundtoftegade’s historical democratic, vivid, and caring way of organizing that is made invisible by the current discourse surrounding the ”Ghetto Law” describing social housing as AKB Lundtoftegade as ”ghettoes”, ”holes in the map of Denmark”, and ”stone deserts”.